Prenatal Cigarette Smoke Exposure Causes Hyperactivity and Agressive Behavior: Role of Altered Catcholamines and BDNF - Yochum, Carrie (2014)
Smoking during pregnancy is associated with a variety of untoward effects on the offspring. However, recent epidemiological studies have brought into question whether the association between neurobehavioral deficits and maternal smoking is causal. We utilized an animal model of maternal smoking to determine the effects of prenatal cigarette smoke (CS) exposure on neurobehavioral development. Pregnant mice were exposed to either filtered air or mainstream CS from gestation day (GD) 4 to parturition for 4 hr/d and 5 d/wk, with each exposure producing maternal plasma concentration of cotinine equivalent to smoking <1 pack of cigarettes per day (25 ng/ml plasma cotinine level). Pups were weaned at postnatal day (PND) 21 and behavior assessed on at 4 weeks of age and again at 4–6 months of age. Male, but not female, offspring of CS-exposed dams demonstrated a significant increase in locomotor activity during adolescence and adulthood that was ameliorated by methylphenidate treatment. Additionally, male offspring exhibited increased aggression, as evidenced by decreased latency to attack and number of attacks in a resident intruder task. These behavioral abnormalities were accompanied by a significant decrease in striatal and cortical dopamine and serotonin and a significant reduction in brain-derived neurotrophic factor (BDNF) mRNA and protein. Taken in concert, these data demonstrate that prenatal exposure to CS produces behavioral alterations in mice that are similar to those observed in epidemiological studies linking maternal smoking to neurodevelopmental disorders and suggest a role for monoaminergic and BDNF alterations in these effects.